Work Less, Party More: A Review Essay about Collaborative Teacher Professional Learning - Jim Parsons (Northwest Journal of Teacher Education, 2013)
This article reviews the positive aspects of teacher collaboration. The author’s latest research focuses specifically upon teacher professional learning and teacher efficacy; and, findings in this research suggest that, of all the reported opportunities for positive professional learning, the highest percentage of teachers note that collaboration with colleagues is the “best” professional learning. In addition, the author’s previous research also had much to say about teacher collaboration. This article synthesizes this research and attempts to pull together foundational understandings that would help articulate “key attributes” of teacher collaboration.